Legal tender in the euro area - Helmut Siekmann (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2018)
With the increasing pressure to abolish cash and the moves to restrict its use, the regulation of legal tender in the primary law of the EU has gained enhanced attention. The core provision is Article 128 TFEU which contains the rules on the issue of banknotes and coins. The author analyzes the terms currency, money, cash, and legal tender in a legal context.
urn:nbn:de:hebis:30:3-475960
Keywords: 330